Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/ange.201901267
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot Assembly for Light‐Driven Multielectron Redox Reactions, such as Hydrogen Evolution and CO2 Reduction

Abstract: Light‐driven multielectron redox reactions (e.g., hydrogen (H2) evolution, CO2 reduction) have recently appeared at the front of solar‐to‐fuel conversion. In this Minireview, we focus on the recent advances in establishing semiconductor quantum dot (QD) assemblies to enhance the efficiencies of these light‐driven multielectron reduction reactions. Four models of QD assembly are established to promote the sluggish kinetics of multielectron transfer from QDs to cocatalysts, thus leading to an enhanced activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…One attractive photocatalytic system should contain TMCs QDs as the PS in place of traditional organic dyes and noble-metal-free complex as the Cat for solar-to-fuel conversion. To make water-soluble QDs, an ultrathin organic ligand layer with an anchoring headgroup tethered to QDs and a hydrophilic tail directed away from the inorganic core, is capped on the QDs surface (Figure b). , The charge transfer from QDs (electron donor) to Cat (electron acceptor) is diffusion-controlled, by which mutual electron delivery is random or indirect (Figure d). However, Li et al found that QDs’ surface defects could be produced as a result of partial loss of surface-capping ligands upon transferring to aqueous solutions.…”
Section: Tmc Qds-organic Moieties Photosystems For H2 Productionmentioning
confidence: 99%
“…One attractive photocatalytic system should contain TMCs QDs as the PS in place of traditional organic dyes and noble-metal-free complex as the Cat for solar-to-fuel conversion. To make water-soluble QDs, an ultrathin organic ligand layer with an anchoring headgroup tethered to QDs and a hydrophilic tail directed away from the inorganic core, is capped on the QDs surface (Figure b). , The charge transfer from QDs (electron donor) to Cat (electron acceptor) is diffusion-controlled, by which mutual electron delivery is random or indirect (Figure d). However, Li et al found that QDs’ surface defects could be produced as a result of partial loss of surface-capping ligands upon transferring to aqueous solutions.…”
Section: Tmc Qds-organic Moieties Photosystems For H2 Productionmentioning
confidence: 99%
“…55,56 Amongst all of these materials, the transition metal quantum dots which have enhanced properties like increased surface area, higher surface to volume ratio, fluorescent properties, conductivity and so on together contributing to an exemplary activity of these materials in electrochemical hydrogen evolution reaction. [57][58][59] Fig. 3(a-b) The "volcano" plot by Trasatti 33 from experimental and the "volcano" plot derived from DFT by Norskov et al 34 Reproduced from ref.…”
Section: Choice Of Transition Metal Quantum Dots As Electrocatalystmentioning
confidence: 99%
“…55,56 Amongst all of these materials, the transition metal quantum dots have enhanced properties such as increased surface area, a higher surface-to-volume ratio, fluorescence properties, and conductivity, together contributing to an exemplary activity of these materials in the electrochemical hydrogen evolution reaction. 57–59…”
Section: Choice Of Transition Metal Quantum Dots As Electrocatalystmentioning
confidence: 99%
See 1 more Smart Citation